PENGARUH SELF-REGULATED LEARNING, EFIKASI DIRI DAN KETERAMPILAN TEKNOLOGI TERHADAP KEBERHASILAN PROGRAM MBKM PADA MAHASISWA AKUNTANSI PERPAJAKAN GEN Z DI SURABAYA - Yasintus Solendro; Gusti Dian Prayogi (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the effect of self-regulated learning on the success of the MBKM program on Generation Z accounting students in Surabaya. Identify the effect of self-efficacy on the success of the MBKM program on Generation Z accounting students in Surabaya. Assess the effect of technological skills on the success of the MBKM program on Generation Z accounting students in Surabaya. Test the simultaneous relationship between self-regulated learning, self-efficacy, and technological skills on the success of the MBKM program on Generation Z accounting students in Surabaya. Data analysis: Descriptive Statistical Test, validity test, reliability test, coefficient of determination test. The object of research in this study is the MBKM program run in universities, especially focusing on student participants in the program who actively participate in various MBKM activities. The success of the MBKM program is measured by various indicators, including students' academic achievement during the program, improvement of technical and non-technical skills, self-regulated learning, self-efficacy, and technology skills possessed by students. The Conclusion is the measurement instruments for the independent variables (Self Regulated Learning, Self Efficacy, Technology Skill) and the dependent variable (Success of the MBKM Program) are declared valid and reliable based on validity and reliability tests. The multiple linear regression model shows that self-regulated learning, self-efficacy and technological skills are proven to influence the success of the MBKM program with self-efficacy being the most dominant variable.